Perancangan Papan Gambar Penghapus Otomatis Menggunakan Mikrokontroler Berbasis Arduino R3 - Rahmi Rismayani Deri; Meilani Pusparita Pratama; Chelsy Dwi Anjani; Mirna Novia Michdan; Siti Julaeha (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Drawing activities on a drawing board are an essential part of the learning process; however, manual erasing often hinders the smooth flow of teaching and learning activities. This study aims to design an automatic drawing board eraser system based on the Arduino R3 microcontroller to improve user efficiency and convenience. The system utilizes a DC motor with bidirectional movement on horizontal and vertical rails, controlled by a TB6600 driver and equipped with a microfiber eraser. The research method employs an engineering experimental approach using a prototyping model, which includes stages of literature review, design, prototype development, testing, and evaluation. The trial was conducted with 20 respondents at SD Negeri Cisero through observation, interviews, and questionnaires. Results show that the system operates stably, responds well to both manual and automatic commands, and is effective in cleaning the board. Out of 200 questionnaire responses, 68.5% of respondents gave positive feedback. In addition, force testing was carried out using a 4 kg load. At a speed of 10 m/s with a 22 cm track length, the resulting force was 2.2 N, whereas at a reduced speed of 8.33 m/s with the same distance, the force increased to 2.6 N. These findings indicate that speed affects the frictional force. The system has proven effective in improving time efficiency and user convenience in educational settings. Keywords: Arduino R3, Automatic eraser, Drawing board, Microcontroller